Consequences of Oil Supply and Demand on the Electricity Market: Coronavirus Effect - Tabachkova, Xenia (International Journal of Energy Economics and Policy, 2021)
The coronavirus epidemic has dealt a serious blow to many sectors of the economy around the globe. The energy sector has dropped significantly and has been affected during the pandemic. The issue of prices for energy products and its production has become aggravated, which has become a test for energy ministries. In this article, it examined the situations in the energy sectors of Europe and Russia as an energy giant. It is difficult at the moment to determine all the impacts that the coronavirus epidemic will have on the electricity sector. The paper found some effects on financial markets in the short term, and others in the longer term. Intuitively, we can already draw the outlines. Electricity is a basic good and as with any public service, it is subject to three principles: continuity, equality of treatment and adaptability. It is the first of them that is vital here. There is no fear on that side, as the operators (EDF, RTE and Enedis) have plans which ensure that nuclear and thermal power plants will maintain their operation - even with 40% absenteeism in the event of a peak of epidemic - and that the networks will be up and running. Priority is given to operational agents, who operate the power plants and repair the power lines. Keywords: COVID, Energy, Electricity, Oil, Demand JEL Classifications: E37, F20, G15 DOI: https://doi.org/10.32479/ijeep.11342